2018
DOI: 10.1200/jco.2017.76.8861
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Mortality From Breast Cancer in Men

Abstract: Purpose Limited data exist on the molecular biology, treatment, and outcomes of breast cancer in men, and much of our understanding in this area remains largely an extrapolation from data in women with breast cancer. Materials and Methods We studied men and women with hormone receptor-positive breast cancer and the 21-gene Breast Recurrence Score (RS) results. Differences in clinical characteristics and gene expression were determined, and distribution of RS results was correlated with 5-year breast cancer-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 31 publications
5
43
0
2
Order By: Relevance
“…Genomic tests, such as Oncotype DX TM , PAM50, and MammaPrint TM , are increasingly being used to determine the prognosis for women with breast cancer and the likelihood that chemotherapy will be beneficial. The results of Oncotype DX testing, a 21gene assay originally developed for FBC that also yields a recurrence score, have been reported in a few studies of MBC (29)(30)(31). The mean quantitative gene expression for genes related to estrogen receptor, proliferation, and invasion was found to be greater in men when compared to women.…”
Section: Discussionmentioning
confidence: 91%
“…Genomic tests, such as Oncotype DX TM , PAM50, and MammaPrint TM , are increasingly being used to determine the prognosis for women with breast cancer and the likelihood that chemotherapy will be beneficial. The results of Oncotype DX testing, a 21gene assay originally developed for FBC that also yields a recurrence score, have been reported in a few studies of MBC (29)(30)(31). The mean quantitative gene expression for genes related to estrogen receptor, proliferation, and invasion was found to be greater in men when compared to women.…”
Section: Discussionmentioning
confidence: 91%
“…Results from the 21-gene breast recurrence score, used to characterize the molecular features of breast cancer, also indicate distinct differences in male compared to female breast cancer. Men below 40 years of age had a higher recurrence score compared to females while above 60 years men had a larger proportion with a low recurrence score [10]. Therefore, although differences between male and female breast cancer become apparent, the crosstalk among predominant biologic pathways and their function in males is not well understood, including that of the HGF/c-MET signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of survival data from randomized trials in male breast cancer, treatment strategies for this disease are largely based upon data from studies of treatment for female breast cancer. In recent years, it becomes clear that the male breast cancer biology may have distinct properties compared to females [8][9][10][11]. Therefore, a better understanding of the breast tumor characteristics in men may help to improve treatment strategies for male breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, research has consistently shown distinct biological differences between male and female breast cancers, including a higher frequency of ER, PR and Bcl-2 gene expression, a lower rate of p53 and Erb-B2 gene expression and an increased incidence of BRCA2 gene mutation in males versus females [ 6 , 7 ]. These differences have been thought to account for variations in pathogenetic evolution and progression of the disease between the sexes [ 7 ]. Despite this knowledge, research and data is still considered limited, rendering the current management of male breast cancers subject to the guidance of female-based algorithms, and thus precluding the development of a standardized screening protocol specific to males.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this knowledge, research and data is still considered limited, rendering the current management of male breast cancers subject to the guidance of female-based algorithms, and thus precluding the development of a standardized screening protocol specific to males. As a result, males, on average, are diagnosed with breast cancer 8–10 years later than females and at a later stage, consequently predisposing them to poorer treatment and prognostic outcomes [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%